1995
DOI: 10.1007/bf00290573
|View full text |Cite
|
Sign up to set email alerts
|

SlyA, a regulatory protein from Salmonella typhimurium, induces a haemolytic and pore-forming protein in Escherichia coli

Abstract: A chromosomal fragment from Salmonella typhimurium, when cloned in Escherichia coli, generates a haemolytic phenotype. This fragment carries two genes, termed slyA and slyB. The expression of slyA is sufficient for the haemolytic phenotype. The haemolytic activity of E. coli carrying multiple copies of slyA is found mainly in the cytoplasm, with some in the periplasm of cells grown to stationary phase, but overexpression of SlyB, a 15 kDa lipoprotein probably located in the outer membrane, may lead to enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
127
2
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(140 citation statements)
references
References 37 publications
8
127
2
3
Order By: Relevance
“…The first 17 amino acids of this protein were characteristic of an N-terminal sec-dependent signal sequence, with a recognition sequence (LVGC) for lipid modification and processing by signal peptidase II (Wu et al, 1983;Yamaguchi et al, 1988). Consistent with this, the predicted protein product shared a high level of sequence identity with Pcp Ye (71%), Pcp Hi (47%) and SlyB (71%), all of which have been classified previously as outer membrane lipoproteins from Yersinia enterocolitica, Haemophilus influenzae and Salmonella typhimurium respectively (Deich et al, 1988;Baumler and Hantke, 1992;Ludwig et al, 1995;Fig. 3).…”
Section: Subcloning and Sequencingsupporting
confidence: 67%
See 1 more Smart Citation
“…The first 17 amino acids of this protein were characteristic of an N-terminal sec-dependent signal sequence, with a recognition sequence (LVGC) for lipid modification and processing by signal peptidase II (Wu et al, 1983;Yamaguchi et al, 1988). Consistent with this, the predicted protein product shared a high level of sequence identity with Pcp Ye (71%), Pcp Hi (47%) and SlyB (71%), all of which have been classified previously as outer membrane lipoproteins from Yersinia enterocolitica, Haemophilus influenzae and Salmonella typhimurium respectively (Deich et al, 1988;Baumler and Hantke, 1992;Ludwig et al, 1995;Fig. 3).…”
Section: Subcloning and Sequencingsupporting
confidence: 67%
“…2) with SlyA, from Salmonella typhimurium, originally classified as a haemolytic virulence factor (salmolysin) required for survival in murine macrophage (Libby et al, 1994). Recently, SlyA has been reclassified as a positive-acting regulatory protein able to induce the production of a cryptic haemolysin in various Escherichia coli strains (Ludwig et al, 1995;Oscarsson et al, 1996). The second of the complete ORFs, orf3 (468 bp) was predicted to encode a 15 540 Da protein of 155 amino acids.…”
Section: Subcloning and Sequencingmentioning
confidence: 99%
“…SlyA of S. enterica has been identified as a member of the MarR/SlyA family, based on the similarity of its amino acid sequence to that of other members of this family (Ludwig et al, 1995;Thomson et al, 1997). Although the amino acid sequence similarity of this SlyA is relatively low, we demonstrated that the structure of this SlyA is very similar to the structures of the other MarR family proteins.…”
Section: Discussionmentioning
confidence: 56%
“…It is interesting to mention that hemolysin E gene although found in non-pathogenic strains of E. coli, it remains silent under laboratory conditions. However, it is positively regulated by several regulatory proteins, which include SlyA and MprA (1,3,(5)(6)(7)(8)). This probably suggests that hemolysin E is expressed in response to appropriate environmental signals.…”
mentioning
confidence: 99%
“…All these data indicate that HlyE similar to other hemolysins (13,14) is likely to be a significant virulence factor responsible for pathogenic infection in human. Experiments in lipid bilayer indicated that hemolysin E forms pores in membrane (4,7). This pore-forming activity of the toxin is considered to be associated with the infection of the pathogenic organism in the target cell.…”
mentioning
confidence: 99%